Pengaruh Motivasi, Semangat Kerja, dan Disiplin Kerja terhadap Kinerja Karyawan PT Pos Indonesia Cabang Kediri - Oni Novea; Indah Listyani; Ahmad Idris (Global Leadership Organizational Research in Management, 2025)
This study aims to examine the influence of motivation, work enthusiasm, and work discipline on the performance of employees at PT. Pos Indonesia (Persero), Kediri Branch Office. A quantitative research approach was employed with a total population of 64 respondents. The sampling technique applied was saturated sampling, resulting in all 64 members of the population being used as the research sample. Data analysis was conducted using SPSS 25.0. The research process included validity and reliability assessments, classical assumption evaluations, multiple linear regression analysis, partial testing (t-test), simultaneous testing (F-test), and calculation of the coefficient of determination (R²). The results reveal that, individually, motivation, work enthusiasm, and work discipline each have a significant impact on employee performance. Moreover, when considered together, these three factors also exert a significant influence on employee performance.